Association of High Expression of Groβ with Clinical and Pathological Characteristics of Unfavorable Prognosis in Gastrointestinal Stromal Tumors. (7th April 2015) - Zhao, Hui; Zhu, Huijun; Jin, Qin; Zhang, Shu; Wang, Wei; Wang, Defeng; Huang, Jianfei
Abstract : GRO β (CXCL2) is a chemokine produced by endotoxin-treated macrophages that mediates inflammation and tumor development. However, little is known about GRO β expression in gastrointestinal stromal tumors (GIST) or the relationship between GRO β expression and clinical attributes of GIST. GRO β expression was examined via immunohistochemical staining of 173 GIST samples using tissue microarray. The relationship between GRO β expression and relevant patient and tumor characteristics was assessed, using chi-square tests. Univariate and multivariate analysis was carried out using the Cox regression method. High GRO β cytoplasm staining was detected in 56 (32.4%) specimens; high GRO β nuclear staining was detected in 64 (37.0%) specimens. High GRO β cytoplasm staining was significantly associated with patients' age (P = 0.043 ) and tumor location (P = 0.014 ), while high GRO β nucleus staining was significantly associated with mitotic index (P = 0.034 ), tumor location (P = 0.049 ), and AFIP-Miettinen risk classification (P = 0.048 ). Kaplan-Meier survival curves showed GIST patients with low GRO β cytoplasm expression (P = 0.023 ) and mitotic index < 6 per 50 HPFs (P = 0.026 ) to have a more favorable prognosis. These findings indicate that GRO β expression correlates with malignant GIST phenotypes and could be an unfavorable prognostic marker in patients with GIST.